Mobile telephone‐delivered contingency management interventions promoting behaviour change in individuals with substance use disorders: a meta‐analysis - Getty, Carol‐Ann; Morande, Ana; Lynskey, Michael; Weaver, Tim; Metrebian, Nicola (Addiction (Abingdon, England), 2019)
Background/aims Contingency management (CM) interventions have gained considerable interest due to their success in the treatment of addiction. However, their implementation can be resource‐intensive for clinical staff. Mobile telephone‐based systems might offer a low‐cost alternative. This approach could facilitate remote monitoring of behaviour and delivery of the reinforcer and minimize issues of staffing and resources. This systematic review and meta‐analysis assessed the evidence for the effectiveness of mobile telephone‐delivered CM interventions to promote abstinence (from drugs, alcohol and tobacco), medication adherence and treatment engagement among individuals with substance use disorders. Design A systematic search of databases (PsychINFO, CINAHL, MEDLINE PubMed, CENTRAL, Embase) for randomized controlled trials and within‐subject design studies (1995–2019). The review was conducted in accordance with the PRISMA statement. The protocol was registered on PROSPERO. Setting All included studies originated in the United states. Participants Seven studies were found, including 222 participants; two targeted alcohol abstinence among frequent drinkers and four targeted smoking cessation (in homeless veterans and those with post‐traumatic stress disorder). One targeted medication adherence. Measures The efficacy of CM to increase alcohol and nicotine abstinence was compared with control using several outcomes; percentage of negative samples (PNS), quit rate (QR) and longest duration abstinent (LDA) at the end of the intervention. Findings The random‐effects meta‐analyses produced pooled effect sizes of; PNS [d = 0.94, 95% confidence interval (CI) = 0.63–1.25], LDA (d = 1.08, 95% CI = 0.69–1.46) and QR (d = 0.46, 95% CI = 0.27–0.66), demonstrating better outcomes across the CM conditions. Most of the studies were rated as of moderate quality. ‘Fail‐safe N' computations for PNS indicated that 50 studies would be needed to produce a non‐significant overall effect size. None could be calculated for QR and LDA due to insufficient number of studies. Conclusion Mobile telephone‐delivered contingency management performs significantly better than control conditions in reducing tobacco and alcohol use among adults not in treatment for substance use disorders.